Pilot study of personalized sleep-coaching messages to promote healthy sleeping behaviors - Schneider, Logan D.; Barakat, Andrew; Ali, Zainab; Concepcion, Christian; Taylor, James A.; Jiang, Allen (Frontiers in Sleep, 2023)
Objectives Assess a program of sleep schedule recommendations and behavior change “nudges” algorithmically selected using passively collected, longitudinal sleep data. Improvements were primarily measured by sleep schedule adherence and changes in sleep health (quantified by the RU_SATED framework). Methods This study used a convenience sample of self-screening volunteers, responding to recruitment emails. Sleep data was gathered with a commercial under-mattress sensor through three phases: baseline passive data collection - 2 weeks; intervention - 4 weeks; maintenance monitoring passive data collection - 8 weeks. The intervention included sleep schedule recommendations and SMS “nudges,” based on rules and recommendations derived from the extant literature. A daily sleep-health score (based on RU_SATED) was derived from passively collected sleep data and daily self-reports of alertness and sleep quality. Results Twenty-six participants (34.92±10.08-years-old; 20M:6F) had adequate data for analysis. The main findings were: 1)Adherence - defined as a wake time (WT) within 30 minutes of the recommendation - rates did not differ significantly between the three study phases. However, there was a general decline in adherence over the course of the study, with adherence rates dropping by about 1.5%/week in a pattern of progressive delay of WTs. 2)Linear mixed models (LMMs) of individual sleep metrics did not demonstrate a significant change over the course of the intervention, possibly due to widely varying, yet relatively healthy, sleep patterns at baseline. 3)Comparatively, the composite, sleep-health (RU_SATED) score demonstrated general improvement over the intervention period, in association with higher rates of WT adherence. Conclusions While, in general, adherence to a sleep schedule and individual dimensions of sleep health did not demonstrate meaningful improvements during the intervention phase, those individuals that were more consistently meeting the wake-time schedule recommendation had associated improvements in their overall sleep-health. As such, this pilot study demonstrates the feasibility and potential efficacy among more adherent individuals of implementing a sleep wellness coaching framework using passively collected sleep data and a rule-based coaching infrastructure.